Childhood Vaccinations and Type 1 Diabetes - Esposito, Susanna; Mariotti Zani, Elena; Torelli, Lisa; Scavone, Sara; Petraroli, Maddalena; Patianna, Viviana; Predieri, Barbara; Iughetti, Lorenzo; Principi, Nicola (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is the most common paediatric endocrine disease, and its frequency has been found to increase worldwide. Similar to all conditions associated with poorly regulated glucose metabolism, T1D carries an increased risk of infection. Consequently, careful compliance by T1D children with schedules officially approved for child immunization is strongly recommended. However, because patients with T1D show persistent and profound limitations in immune function, vaccines may evoke a less efficient immune response, with corresponding lower protection. Moreover, T1D is an autoimmune condition that develops in genetically susceptible individuals and some data regarding T1D triggering factors appear to indicate that infections, mainly those due to viruses, play a major role. Accordingly, the use of viral live attenuated vaccines is being debated. In this narrative review, we discussed the most effective and safe use of vaccines in patients at risk of or with overt T1D. Literature analysis showed that several problems related to the use of vaccines in children with T1D have not been completely resolved. There are few studies regarding the immunogenicity and efficacy of vaccines in T1D children, and the need for different immunization schedules has not been precisely established. Fortunately, the previous presumed relationship between vaccine administration and T1D appears to have been debunked, though some doubts regarding rotavirus vaccines remain. Further studies are needed to completely resolve the problems related to vaccine administration in T1D patients. In the meantime, the use of vaccines remains extensively recommended in children with this disease.